2015
DOI: 10.1002/2015jd024059
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the performance of the Beijing Climate Centre Climate System Model 1.1(m) to simulate precipitation across China based on long‐range correlation characteristics

Abstract: In this study, we investigated the observed daily precipitation data in China using detrended fluctuation analysis. The daily precipitation records exhibit relatively weak long‐range correlation (LRC) characteristics with scaling exponents of less than 0.6 in most of China. The performance of the climate model can be quantitatively evaluated by comparing the differences of the scaling exponents between the observational data and the model‐simulated data. Based on these findings, the performance of the Beijing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…In this study, DFA2 is used (Kantelhardt et al, 2001). To estimate the uncertainties of the DFA2 method, we conducted six sets of independent tests for six given scaling exponents according to Zhao and He (2015b). In each test, Fourier-filtering method (FFM, Peng et al, 1991) produced 20 000 artificial time series with given scaling exponents.…”
Section: Detrended Fluctuation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, DFA2 is used (Kantelhardt et al, 2001). To estimate the uncertainties of the DFA2 method, we conducted six sets of independent tests for six given scaling exponents according to Zhao and He (2015b). In each test, Fourier-filtering method (FFM, Peng et al, 1991) produced 20 000 artificial time series with given scaling exponents.…”
Section: Detrended Fluctuation Analysismentioning
confidence: 99%
“…The LRC of a climate system is the theoretical basis for long-term climate predictions (Huang et al, 1993;Dong, 2003, 2004;Ding and Li, 2007;Li and Wang, 2008;Ding, 2011, 2013). Detrended fluctuation analysis (DFA) is a nonlinear approach to detect LRC in time series based on random processes and chaos theory (Peng et al, 1994); it has been used to evaluate the dynamic characteristics of climate system models (Blender and Fraedrich, 2003;Zhao and He, 2014, 2015a, 2015b. In 2002, Govindan et al (2002) found that seven leading global climate models (GCMs) fail to reproduce the universal scaling behaviour of the observed temperature records for two different scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…BCC-CSM2 is a fully coupled global CSM in which the atmosphere, land, ocean, and sea-ice components interact with each other through the exchange of momentum, energy, water, and carbon (Wu et al, 2008(Wu et al, , 2013(Wu et al, , 2019. The earlier version of BCC-CSM (v1.1 and v1.1m) was enrolled in CMIP5 and has been widely applied on weather and climate research (e.g., Wu et al, 2013Wu et al, , 2014Xin et al, 2013;Zhao and He, 2015). It has been recently updated to BCC-CSM2 and is being used in that configuration for the Coupled Model Intercomparison Project Phase 6 (CMIP6) (Wu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its advantages and applicability (Bashan et al 2008), this method has been widely used in the meteorological field in recent years (Kantelhardt et al 2006;Fraedrich et al 2009;Zhu et al 2010;Bunde et al 2013;Jiang et al 2015;Yuan et al 2015;He et al 2016;Jiang et al 2017). With the extensive usage of climate models, people begin to use the DFA method to assess merits of climate models by comparing the difference of scaling exponents between the simulated data of climate models and observed data (Govindan et al 2002;Zhao and He 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Zhao and He produced 20000 artificial series with the given scaling exponents by Fourier Filtering in order to test the uncertainties of DFA method. Results of the artificial series indicate that the uncertainties of DFA method range from −0.05 to 0.05 for the precipitation series (Zhao and He 2015). For convenience, this article defines the deviation ranging from −0.05 to 0.05 as the 0.1 significant test level of precipitation series over the Qinghai-Tibet Plateau.…”
Section: Introductionmentioning
confidence: 99%